Research Trend on Business Innovation Using Bibliometric Analysis with VOSviewer - Dika Putra Wijaya; Mohammad Kawtsar; Manon Guiny; Ganesh Ganesh; Nur Laila; Wirda Amirotul Amiroh (Universitas Syiah Kuala, 2026)
This study aims to map global research trends and identify dominant thematic clusters within the business innovation literature to provide a comprehensive structural framework. Using a descriptive bibliometric approach, publication data spanning from 2022 to 2026 was retrieved from a premier scientific database to evaluate emerging literature patterns and keyword linkages. The findings reveal three core thematic clusters internal dimensions, organizational outcomes, and macro contexts with